Internal Service Quality of the Purchasing Department: Its Relationship with Internal Customer Satisfaction, Performance, and the Moderating Role of Organizational Culture - Putri Handayani Sirait; Tommy C. Efrata; Damelina Basauli Tambunan (Politeknik Siber Cerdika Internasional, 2026)
Background: In the context of the animal feed manufacturing industry in Indonesia, the purchasing function plays a strategic role in providing operational raw materials; however, its performance evaluation often overlooks internal service aspects. Objective: This study aims to analyze the influence of the purchasing department’s internal service quality on internal customer satisfaction and performance, with organizational culture serving as a moderating variable. Methods: A quantitative survey-based approach was employed, involving 175 internal customers from the Production, Quality Control, Finance, Marketing, and Warehouse departments of an Indonesian animal feed manufacturing company. Respondents were selected using purposive sampling. Data were collected through a structured questionnaire based on SERVQUAL dimensions and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to examine direct, mediating, and moderating relationships. Results: The results demonstrate that the purchasing department’s internal service quality has a positive and significant effect on internal customer satisfaction (β = 0.903, p < 0.001) and internal customer performance (β = 0.252, p = 0.017). Internal customer satisfaction significantly mediates the relationship between the purchasing department’s internal service quality and internal customer performance (β = 0.517, p < 0.001). However, organizational culture does not moderate the relationships between internal service quality and satisfaction (β = −0.036, p = 0.174) or performance (β = −0.027, p = 0.182). Conclusion: This study extends SERVQUAL to the internal purchasing function in Indonesian manufacturing and shows that internal customer satisfaction fully mediates the relationship between service quality and performance. Managers should monitor internal service quality and strengthen purchasing staff's interpersonal skills to improve cross-functional performance.